Apuntes sobre el territorio y la creación : vidas de Alan Pauls - Teresa Orecchia Havas (Cuadernos LIRICO)
Alan Pauls introduces the concept of « expanded literature » in a remarkable 2008 year essay. The concept, based on the example of the avant-gardes and of authors such as Bellatín, Aira o Libertella, allows him to propose his own vision of the relationship between the writer’s work and life. This article compares the essay’s ideas with Pauls’s poetics of narration, by analyzing the set of novels ranging from Wasabi to the cycle of the Historia(s)…. The purpose is to propose a frame enough comprehensive to understand that the esthetical ideas developed in the essay and the narrative fiction are built as a map based rather on convergences and divergences than on antagonistic hypothesis. The article focuses on the fictional representations of the creative process and shows that the narration reveals great trust in the hermeneutical value of signs and language.